Intensity of antigen expression reflects IGHV mutational status and Dohner-defined prognostic categories in chronic lymphocytic leukemia, monoclonal B-cell lymphocytosis, and small lymphocytic lymphoma. Issue 8 (3rd July 2021) - Balakrishna, Jayalakshmi; Basumallik, Neil; Matulonis, Robert; Scott, Drake; Salem, Dalia; Jasper, Gregory; Wiestner, Adrian; Stetler-Stevenson, Maryalice; Marti, Gerald; Sun, Clare; Yuan, Constance M.
Abstract: We demonstrate the prognostic utility of antigen quantitation in chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) and monoclonal B-cell lymphocytosis (MBL). Median antibody-bound-per-cell (ABC) of CD20, CD22, CD25, CD19, and %CD38(+) was determined in CLL (185/208), SLL (8/208) and MBL (15/208) cases by flow cytometry, then compared to Dohner-classification, immunoglobulin status (mutated, IGHV-M; unmutated, IGHV-U), CLL-IPI risk and time to first treatment (TTFT). Trisomy 12 cases showed increased %CD38-expression ( p = .0379). Higher %CD38 was observed in IGHV-U versus IGHV-M ( p = .0003). CD20ABC was increased in IGHV-U versus IGHV-M ( p = .006). Del13q cases demonstrated lower CD22ABC ( p = .0198). Cases without cytogenetic abnormality exhibited higher CD19ABC ( p = .0295) and CD22ABC ( p = .0078). Del17p cases demonstrated lower CD25ABC ( p = .0097). High and very-high CLL-IPI risk groups were associated with high CD38-expression ( p = .02) and low CD25ABC ( p = .0004). Shortened TTFT was associated with high CD38-expression ( p < .0001). Interestingly, high CD25ABC trended toward shortened TTFT ( p = .07). Quantitative antigen expression reflects CLL-IPI risk groups and Dohner-classification.